Magellanic penguin mortality in 2008 along the SW Atlantic coast - Garcia Borboroglu, Jorge Pablo (2010)
Magellanic penguins migrate from Patagonia reaching northern Argentina, Uruguay, and southern Brazil on their winter migration, in parallel with the seasonal pulse of anchovy spawning. In 2008, Magellanic penguins went further north than usual. Many died and a few swam nearly to the Equator. Twelve groups surveyed 5000. km of coastline encountering 3371 penguins along the coast. Most penguins arrived in northern Brazil (68.4%) without petroleum (2933, 87%). Almost all penguins without petroleum were juveniles (2915, 99%) and 55% were alive when found. Penguins were dehydrated, anemic, hypothermic, and emaciated. Of the penguins with petroleum, 13% arrived in the southern half of Brazil, showing that petroleum pollution remains a problem along the SW Atlantic coast. The mortality occurred in the winter of 2008 when sea surface temperature were unusually cold perhaps reducing the prey for penguins.